Alkali treatment of Gracilaria coronopifolia Its effect on the gel strength and yield of agar - Maglasin , Johnna Grace Camacho
The effect of varying NaOH concentration (1%, 3%, 5%) and duration of pretreatment (30, 60, 75 min.) of alkali pretreatment of seaweed, Gracilaria coronopifolia on the yield and gel strenght of agar was evaluated.